CMV-infection in patients after liver transplantation - M. Sh. Khubutiya; V. E. Syutkin; A. A. Salienko; M. S. Novruzbekov (Трансплантология (Москва), 2016)
The article presents an analysis of the current state of the problem antiviral therapy CMV-infection in patients undergoing liver transplantation. We retrospectively reviewed the experience of the Moscow Center for liver transplantation in the prevention of cytomegalovirus disease in liver recipients. We describe the clinical examples of different flow CMV-infection in patients after liver transplantation and therapy approaches.